2015
DOI: 10.1177/1078345814557788
|View full text |Cite
|
Sign up to set email alerts
|

Screening Incarcerated Juveniles Using the MAYSI-2

Abstract: The high prevalence of mental health disorders among incarcerated juveniles is a matter of national and global concern. Juvenile justice personnel need accurate screening measures that identify youth requiring immediate mental health services. The purpose of this study was threefold: (a) to examine the utility of the Massachusetts Youth Screening Instrument, Version 2 (MAYSI-2) in identifying juveniles with mental health concerns in a large sample of juveniles (N = 4,009), (b) to provide data regarding rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…An alarming number of adolescents in juvenile custody have been found to have mental health disorders (Gilbert et al, 2015; Teplin et al, 2013). In fact, adolescents in custody have disproportionately higher mental health disorders compared to those in the general population (Gilbert et al, 2015; Teplin et al, 2013). It is necessary to identify risk and protective factors for psychological distress to create effective intervention and prevention programs and policies.…”
Section: Discussionmentioning
confidence: 99%
“…An alarming number of adolescents in juvenile custody have been found to have mental health disorders (Gilbert et al, 2015; Teplin et al, 2013). In fact, adolescents in custody have disproportionately higher mental health disorders compared to those in the general population (Gilbert et al, 2015; Teplin et al, 2013). It is necessary to identify risk and protective factors for psychological distress to create effective intervention and prevention programs and policies.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates reveal that approximately 50 to 75 percent of the 2 million youth encountering the juvenile justice system meet criteria for a mental health disorder [6,16,21,22,23]. Approximately 40 to 80 percent of incarcerated juveniles have at least one diagnosable mental health disorder [16,24,25,26,27]. Two-thirds of males and three-quarters of females in previous studies of juvenile offender detention facilities, were found to meet criteria for at least one mental health disorder [26,28,29,30].…”
Section: Mental Health Concerns For Youth In the Juvenile Justice mentioning
confidence: 99%
“…Of these studies, one, like ours, found that on all five of the MAYSI‐2 scales rateable by boys and girls (excluding TE as it has no cut‐off), the latter had higher scores (Cauffman, ). Although Archer et al () and Gilbert et al () also reported this, it is not clear that the differences they found were statistically significant. Five (Grisso et al, ; Hayes et al, ; Cauffman et al, ; Kerig et al, ) and one unpublished doctoral thesis (Maney, ) found girls have higher scores on all scales apart from the substance (ADU) scale.…”
Section: Discussionmentioning
confidence: 82%